2017
DOI: 10.1051/0004-6361/201730514
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid modelling of cometary plasma environments

Abstract: Context. The ESA/Rosetta mission made it possible to monitor the plasma environment of a comet, from near aphelion to perihelion conditions. To understand the complex dynamics and plasma structures found at the comet, a modelling effort must be carried out in parallel. Aims. Firstly, we present a 3D hybrid model of the cometary plasma environment including photoionisation, solar wind charge exchange, and electron ionisation reactions; this model is used in stationary and dynamic conditions (mimicking the solar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 112 publications
0
43
0
Order By: Relevance
“…Lengths are in units of 10 5 km solar wind Mach number diminishes and/or gas production rate increases. Recent models show that the dimensions of the bowshock increase with greater photoionization, chargeexchange, and electron impact ionization (Simon Wedlund et al 2017). Consequently, the dimensions of the magnetosheath region of shocked solar wind plasma behind the dayside bow shock should also increase as comets move sunward and sublimation increases (Flammer 1991).…”
Section: Cometsmentioning
confidence: 99%
“…Lengths are in units of 10 5 km solar wind Mach number diminishes and/or gas production rate increases. Recent models show that the dimensions of the bowshock increase with greater photoionization, chargeexchange, and electron impact ionization (Simon Wedlund et al 2017). Consequently, the dimensions of the magnetosheath region of shocked solar wind plasma behind the dayside bow shock should also increase as comets move sunward and sublimation increases (Flammer 1991).…”
Section: Cometsmentioning
confidence: 99%
“…During this period, attempts to detect the bow shock were mostly unsuccessful because the spacecraft most of the time orbited in the inner coma (see e.g. Simon Wedlund et al 2017). Recently, Gunell et al (2018) reported measurements from the Rosetta Plasma Consortium (RPC) instrument suite onboard Rosetta, which for the first time showed evidence that the cometary bow shock was in a formation process at a heliocentric distance of about 2.3 AU.…”
Section: Introductionmentioning
confidence: 99%
“…This implies that in the simplistic assumption of a rectilinear motion along the Suncomet line of the incoming solar wind ions, the retrieved solar wind upstream flux will be underestimated by this method. Selfconsistent modeling taking into account all charge-changing reactions, using hybrid (Simon Wedlund et al 2017) or multi-fluid MHD models (Huang et al 2016), can overcome this caveat.…”
Section: Upstream Solar Wind Fluxmentioning
confidence: 99%
“…Comparison with in situ derived outgassing rates by the Rosetta Orbiter Spectrometer for Ion and Neutral Analysis Comet Pressure Sensor (ROSINA-COPS) (Balsiger et al 2007) showed that with these simple assumptions, month-to-month differences between the RPC-ICA-inferred and ROSINA-measured water outgassing rates remained within a factor 2 − 3 (Hansen et al 2016). In parallel, using a new quasi-neutral hybrid model of the cometary plasma environment, Simon Wedlund et al (2017) studied the interplay between ionization processes in the formation of boundaries at comet 67P. They showed that CX plays a major role at large cometocentric distances (> 1000 km at a heliocentric distance of 1.3 AU), whereas photoionization and electron ionization (sometimes referred to as "electron impact ionization") is the main source of new cometary ions in the inner coma (Bodewits et al 2016).…”
Section: Introductionmentioning
confidence: 99%